2009
DOI: 10.1159/000204229
|View full text |Cite
|
Sign up to set email alerts
|

Nurr1 Expression and Its Modulation in Microglia

Abstract: Objective:Nurr1, a transcription factor essential for the differentiation and maturation of central dopaminergic cells, is primarily expressed in neurons of the central nervous system. In this study, we intend to determine the expression and modulation of Nurr1 in cultured microglia. Methods: Nurr1 expression in cultured primary mouse microglia was measured by reverse transcription polymerase chain reaction, Western blot and immunofluorescent staining. Lipopolysaccharide (LPS) was used to activate microglia. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 96 publications
1
23
0
Order By: Relevance
“…Although several potential mechanisms for this neuroprotection are possible, the ability of valproate to increase Nurr1 expression and binding to promoter regions of catecholamine genes, including the DAT, tyrosine hydroxylase and the vesicular monoamine transporter 2 (Smits et al, 2003) may result in maintenance of these phenotypic markers of dopamine neurons during neurodegeneration. Moreover, Nurr1 has recently been demonstrated to play an important role in dampening neuroinflammation through its action in microglia (Fan et al, 2009; Saijo et al, 2009), which would be expected to be protective in Parkinson’s disease. Additional studies will be required to determine the relative roles of these potential mechanisms in the neuroprotective effects of valproate.…”
Section: Discussionmentioning
confidence: 99%
“…Although several potential mechanisms for this neuroprotection are possible, the ability of valproate to increase Nurr1 expression and binding to promoter regions of catecholamine genes, including the DAT, tyrosine hydroxylase and the vesicular monoamine transporter 2 (Smits et al, 2003) may result in maintenance of these phenotypic markers of dopamine neurons during neurodegeneration. Moreover, Nurr1 has recently been demonstrated to play an important role in dampening neuroinflammation through its action in microglia (Fan et al, 2009; Saijo et al, 2009), which would be expected to be protective in Parkinson’s disease. Additional studies will be required to determine the relative roles of these potential mechanisms in the neuroprotective effects of valproate.…”
Section: Discussionmentioning
confidence: 99%
“…Following LPS stimulation, the expression levels of Nurr1 were markedly increased, which could be blocked by inhibitors of ERK, JNK and PI3K/Akt. The ERK inhibitor was shown to partially block the translocation of Nurr1 from the cytoplasm to the nucleus (163). Bensinger and Tontonoz (164) also indicated that Nurr1 protects DA neurons by suppressing inflammatory gene expression in astrocytes and microglia.…”
Section: Transcriptional Regulation Of Inflammatory Processesmentioning
confidence: 99%
“…This indicated that ROP might exert neuroprotective effects through the PI3K pathway, and that PIK3C2B might play a role in this process. Additionally, we previously observed that the PI3K/Akt pathway modulates the expression of Nurr1, which is a transcription factor essential for the differentiation and maturation of central dopaminergic cells ( 15 ). This suggested that ROP might induce PIK3C2B and modulate Nurr1 to exert neuroprotection.…”
Section: Discussionmentioning
confidence: 99%